In Vivo High-Resolution MR Imaging of Neuropathologic Changes in the Injured Rat Spinal Cord - Weber, T. (AJNR Am J Neuroradiol, 2006)
BACKGROUND AND PURPOSE: MR imaging is the most comprehensive noninvasive means to assess structural changes in injured central nervous system (CNS) tissue in humans over time. The few published in vivo MR imaging studies of spinal cord injury in rodent models by using field strengths ≤7T suffer from low spatial resolution, flow, and motion artifacts. The aim of this study was to assess the capacity of a 17.6T imaging system to detect pathologic changes occurring in a rat spinal cord contusion injury model ex vivo and in vivo. METHODS: Seven adult female Fischer 344 rats received contusion injuries at thoracic level T10, which caused severe and reproducible lesions of the injured spinal cord parenchyma. Two to 58 days postinjury, high-resolution MR imaging was performed ex vivo (2) or in vivo in anesthetized rats (5 spinal cord injured + one intact control animal) by using 2D multisection spin- and gradient-echo imaging sequences, respectively, combined with electrocardiogram triggering and respiratory gating. RESULTS: The acquired images provided excellent resolution and gray/white matter differentiation without significant artifacts. Signal intensity changes, which were detected with ex vivo and in vivo MR imaging following spinal cord injury, could be correlated with histologically defined structural changes such as edema, fibroglial scar, and hemorrhage. CONCLUSIONS: These results demonstrate that MR imaging at 17.6T allows high-resolution structural analysis of spinal cord pathology after injury.